1991
DOI: 10.1021/bi00100a007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of DNA with the Klenow fragment of DNA polymerase I studied by time-resolved fluorescence spectroscopy

Abstract: The interaction of a fluorescent duplex DNA oligomer with the Klenow fragment of DNA polymerase I from Escherichia coli has been studied in solution by using time-resolved fluorescence spectroscopy. An aminonaphthalenesulfonate (dansyl) fluorescent probe was linked by a propyl chain to a C5-modified uridine base located at a specific site in the primer strand of the DNA oligomer. The fluorescent oligomer bound tightly to the Klenow fragment (KD = 7.9 nM), and the probe's position within the DNA-protein complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 28 publications
8
122
0
Order By: Relevance
“…The labeling of Tyr766 by a photoaffinity probe at the primer terminus is likewise consistent with the general location of the polymerase catalytic site (57). Chemical footprinting (58), fluores cence (59,60), and photocrosslinking (57) experiments together indicate that 5-8 basepairs of duplex DNA are covered by Klenow fragment when the primer terminus is at the polymerase site. The range of values probably reflects, on the one hand, the particular requirements for access of the footprinting reagent and, on the other, uncertainties as to the precise orientation of fluorescent or photoactivatable probes attached to DNA; again, the data are consistent with the proposed model but are insufficiently discriminating to rule out alternatives that could be proposed.…”
Section: Binding Of Primer-templatesupporting
confidence: 55%
See 2 more Smart Citations
“…The labeling of Tyr766 by a photoaffinity probe at the primer terminus is likewise consistent with the general location of the polymerase catalytic site (57). Chemical footprinting (58), fluores cence (59,60), and photocrosslinking (57) experiments together indicate that 5-8 basepairs of duplex DNA are covered by Klenow fragment when the primer terminus is at the polymerase site. The range of values probably reflects, on the one hand, the particular requirements for access of the footprinting reagent and, on the other, uncertainties as to the precise orientation of fluorescent or photoactivatable probes attached to DNA; again, the data are consistent with the proposed model but are insufficiently discriminating to rule out alternatives that could be proposed.…”
Section: Binding Of Primer-templatesupporting
confidence: 55%
“…The range of values probably reflects, on the one hand, the particular requirements for access of the footprinting reagent and, on the other, uncertainties as to the precise orientation of fluorescent or photoactivatable probes attached to DNA; again, the data are consistent with the proposed model but are insufficiently discriminating to rule out alternatives that could be proposed. Using time resolved fluorescence spectroscopy, it has been concluded that more of the duplex DNA upstream of the primer terminus is drawn into the binding site when the 3' terminus is at the 3'-5' exonuclease active site (60). The proposed model (19) suggests a difference of 2-3 basepairs between the polymerase and exonuclease binding modes; it does not appear able to accommodate the 9-nucleotide difference inferred from experiments that compared the effect of a bulky DNA substituent on the two enzymatic reactions (61).…”
Section: Binding Of Primer-templatementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the interaction of the replicative DNA polymerase is, of necessity, confined to the primertemplate junction. The polymerase has a high affinity for this unique structure over either ssDNA or double-stranded DNA (4,5). The processivity of the polymerase is further enhanced by the sliding clamp family of proteins that tether the polymerase to the DNA (6,7).…”
mentioning
confidence: 99%
“…1B) and forming a 7-base duplex structure with itself that can initiate replication. The 15mer thrombin aptamer appears to have a dissociation constant (K d ) from 25 to 200 nmol/L for thrombin (26 ), whereas the Klenow fragment polymerase has a K d of 7.9 nmol/L for DNA (27 ). The thrombin aptamer has a greater K d for thrombin than the polymerase for DNA, so the polymerase is able to displace thrombin from the furled-up pocket on the 5Ј terminus.…”
Section: Methodsmentioning
confidence: 99%